2021
DOI: 10.3390/ma14206172
|View full text |Cite
|
Sign up to set email alerts
|

Metaheuristic Prediction of the Compressive Strength of Environmentally Friendly Concrete Modified with Eggshell Powder Using the Hybrid ANN-SFL Optimization Algorithm

Abstract: The aim of this article is to predict the compressive strength of environmentally friendly concrete modified with eggshell powder. For this purpose, an optimized artificial neural network, combined with a novel metaheuristic shuffled frog leaping optimization algorithm, was employed and compared with a well-known genetic algorithm and multiple linear regression. The presented results confirm that the highest compressive strength (46 MPa on average) can be achieved for mix designs containing 7 to 9% of eggshell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…In this case, the optimal dosage of eggshell powder as a replacement for part of the cement is 10%, as in [13,16,19,21], but the performance gains achieved in these works differ. The optimal dosages of ESP according to [10,13,16,18,[20][21][22] are from 5 to 15%. However, sometimes there are also more optimal amounts of added ESP, for example, 20% [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the optimal dosage of eggshell powder as a replacement for part of the cement is 10%, as in [13,16,19,21], but the performance gains achieved in these works differ. The optimal dosages of ESP according to [10,13,16,18,[20][21][22] are from 5 to 15%. However, sometimes there are also more optimal amounts of added ESP, for example, 20% [15].…”
Section: Discussionmentioning
confidence: 99%
“…Additive [10] The addition of eggshell powder in an amount of 7-9% by weight of cement provides an increase in compressive strength up to 55% in comparison with the strength characteristics of samples of Portland cement. [11] According to the results of the study, it was found that the addition of powder in an amount of 15% is the most optimal and provides a decrease in water absorption up to 30%, an increase in compressive strength up to 29%, and a decrease in the thermal conductivity index up to 40% in comparison with similar indicators for samples of the control composition.…”
Section: The Role Of Eggshell In Concrete Source Influence Of Eggshel...mentioning
confidence: 99%
“…The problems, in turn, arising in the enterprises of the construction industry are expressed in manufacturing defects and the imperfection of prescription and technological factors that affect the quality of the resulting concrete, as well as in factors such as the influence of the human factor, errors in the selection of compositions, the production of concrete, and their assessment in terms of the ratio of initial parameters and output parameters. In this regard, it also implies the digitalization of all branches of modern industry, the application of artificial intelligence in the construction industry, and in particular, in concrete technology, which contains many vectors and directions for digitalization and improvement of properties, is seen as a relevant direction [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Currently, one of the relevant areas among artificial intelligence methods in industrial production is neural networks, which allow one to create systems for predicting output parameters, that is, the operational properties of any products, structures, buildings and structures that depend on the characteristics of the initial components and process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The studies performed on environmentally friendly and sustainable composites recently have gained importance. Tosee et al [13] investigated the compressive strength of environmentally friendly concrete modified with eggshell powder using the hybrid ANN-SFL optimization algorithm. They found that the highest compressive strength was obtained for the samples containing 7-9% of eggshell powder and it was 55% higher than their control samples.…”
Section: Introductionmentioning
confidence: 99%